Effect Of Different Glycerol Levels In Egg Yolk Citrate Extender On Freezability Of Ram Semen - Sardar, V.M.; Bonde, S.W.; Patodkar, V.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
An experiment was carried out to evaluate the optimum glycerol level in egg yolk citrate diluent on freezability of ram semen. The ejaculates were obtained from six crossbred rams (Malpura X Bharat Merino). The semen was diluted with the diluent containing different levels of glycerol (4, 6, 8 and 10 %) and was frozen in liquid nitrogen at -196°C. The post-thaw motility and live sperm per cent were higher at 6 per cent glycerol level as compared to 8 per cent glycerol level. The values of post-thaw dead and abnormal sperm per cent were significantly lower at 6 per cent glycerol level as compared to 8 per cent glycerol level.